KETERKAITAN INDEKS PEMBANGUNAN MANUSIA KABUPATEN/KOTA DI SULAWESI UTARA DENGAN PERTUMBUHAN EKONOMI - Christine V. Manoppo; Esry O.H. Laoh; Yolanda P.I. Rori (Universitas Sam Ratulangi, 2015)
ABSTRACT This study aims to look the human development index linkage of district / city in North Sulawesi with economic growth in the period 2008-2013. This research is motivated by the importance of human development in promoting economic growth. The research was conducted from May 2015 through July 2015 and uses sekunder data, data used in the form of data Economic Growth and Human Development Index districts / city in North Sulawesi from 2008-2013 year were obtained from the Central Bureau of Statistics North Sulawesi. Analysis of the data used in this research is descriptive analysis presented in tables and quadrants. Results of the study describes the state of economic growth and Human Development Index districts / cities in North Sulawesi during the years 2008-2013. The results showed economic growth is not always in line with the human development index, during the years 2008-2013 remain areas that showed economic growth is above average but below the human development index and vice versa average economic growth below average and indices human development above average. Keywords: Economic Growth, Human Development Indeks